2018
DOI: 10.1101/263079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tailored perception: listeners’ strategies for perceiving speech fit their individual perceptual abilities

Abstract: Communicative auditory signals express their structure through acoustic dimensions such as pitch and timing. Individuals' abilities to perceive these dimensions vary widely, and yet most people seem to comprehend music and speech easily. How?Here we tested whether redundancy -multiple acoustic cues indexing the same feature -makes music and speech robust to such individual differences. A model population with a severe and specific deficit for perceiving pitch (congenital amusics) and controls completed 3 tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…By lowering the barrier, Gorilla aims to make online experiments available and transparent at all levels of ability. Currently, experiments have been conducted in Gorilla on a wide variety of topics, including cross-lingual priming (Poort & Rodd, 2017), the provision of lifestyle advice for cancer prevention (Usher-Smith et al, 2018), semantic variables and list memory (Pollock, 2018), narrative engagement (Richardson et al, 2018), trust and reputation in the sharing economy (Zloteanu, Harvey, Tuckett, & Livan, 2018), how individuals' voice identities are formed (Lavan, Knight, & McGettigan, 2018), and auditory perception with degenerated music and speech (Jasmin, Dick, Holt, & Tierney, 2018). Also, several studies have preregistered reports, including explorations of object size and mental simulation of orientation (Chen, de Koning, & Zwaan, 2018) and the use of face regression models to study social perception (Jones, 2018).…”
Section: The Gorilla Experiments Buildermentioning
confidence: 99%
“…By lowering the barrier, Gorilla aims to make online experiments available and transparent at all levels of ability. Currently, experiments have been conducted in Gorilla on a wide variety of topics, including cross-lingual priming (Poort & Rodd, 2017), the provision of lifestyle advice for cancer prevention (Usher-Smith et al, 2018), semantic variables and list memory (Pollock, 2018), narrative engagement (Richardson et al, 2018), trust and reputation in the sharing economy (Zloteanu, Harvey, Tuckett, & Livan, 2018), how individuals' voice identities are formed (Lavan, Knight, & McGettigan, 2018), and auditory perception with degenerated music and speech (Jasmin, Dick, Holt, & Tierney, 2018). Also, several studies have preregistered reports, including explorations of object size and mental simulation of orientation (Chen, de Koning, & Zwaan, 2018) and the use of face regression models to study social perception (Jones, 2018).…”
Section: The Gorilla Experiments Buildermentioning
confidence: 99%
“…By lowering the barrier, Gorilla aims to make online experiments available and transparent at all levels of ability. Currently, experiments have been conducted in Gorilla on a wide variety of topics, including: cross-lingual priming (Poort & Rodd, 2017), the provision of lifestyle advice for cancer prevention (Usher-Smith et al, 2018), semantic variables and list 12 memory (Pollock, 2018), narrative engagement (Richardson et al, 2018), trust and reputation in the sharing economy (Zloteanu, Harvey, Tuckett, & Livan, 2018), how individual's voice identities are formed (Lavan, Knight, & McGettigan, 2018), and auditory perception with degenerated music and speech (Jasmin, Dick, Holt, & Tierney, 2018). Also, several studies have pre-registered reports, including: object size and mental simulation of orientation (Chen, de Koning, & Zwaan, 2018) and the use of face regression models to study social perception (Jones, 2018).…”
Section: The Gorilla Experiments Buildermentioning
confidence: 99%
“…This suggests that impairments in pitch versus duration perception, which have been shown to be dissociable (Hyde & Peretz, 2004;Kidd et al, 2007), may not have equal effects on different aspects of prosody perception. For example, individuals with impaired pitch perception may have greater difficulties with the perception of linguistic focus than with phrase boundary perception, as we have demonstrated in amusics (Jasmin et al, 2018).…”
Section: The Role Of Pitch and Durational Cues In Focus And Phrase Pementioning
confidence: 54%
“…Listeners can make use of such prosodic cues to clarify potentially ambiguous syntactic structures in a sentence (Beach, 1991;Frazier, Carlson, & Clifton Jr, 2006;Lehiste, Olive, & Streeter, 1976;Marslen-Wilson, Tyler, Warren, Grenier, & Lee,, 1992;Jasmin, Dick, Holt, & Tierney, 2018). In fact, prosodic patterns may be a more powerful cue to phrase structure than statistical patterns, as artificial grammar learning experiments have shown that when prosodic cues and transitional probabilities are pitted against one another, listeners will learn hierarchical structure which reflects prosodic information (Langus, Marchetto, Bion, & Nespor, 2012).…”
Section: Multiple Dimensions For Prosodymentioning
confidence: 99%
See 1 more Smart Citation